Analisis Tingkat Kepuasan Petani Terhadap Kinerja Penyuluh Pertanian Lapangan di Kabupaten Aceh Barat - Ida Armayanti (LANCAH: Jurnal Inovasi dan Tren, 2023)
This research was conducted to analyze the level of farmer satisfaction with the performance of Field Agricultural Extension in Johan Pahlawan District, West Aceh Regency. The location in the research was conducted in Johan Pahlawan District, West Aceh Regency, with the total population taken being all rice farmer groups in Johan Pahlawan District, West Aceh Regency. The sampling method was carried out using stratified random sampling. The data analysis method used in this study is to use quantitative analysis and data analysis using simple linear regression analysis. To analyze the respondent's level of agreement, it is measured using a Likert scale. The results of the study found that farmer satisfaction can be significantly influenced by field agricultural extension performance variables in the sense that field agricultural extension performance variables are factors that can significantly increase farmer satisfaction in Johan Pahlawan District, West Aceh Regency.